SCN3A‐Related Neurodevelopmental Disorder: A Spectrum of Epilepsy and Brain Malformation. Issue 2 (9th July 2020) - Zaman, Tariq; Helbig, Katherine L.; Clatot, Jérôme; Thompson, Christopher H.; Kang, Seok Kyu; Stouffs, Katrien; Jansen, Anna E.; Verstraete, Lieve; Jacquinet, Adeline; Parrini, Elena; Guerrini, Renzo; Fujiwara, Yuh; et al.
Abstract : Objective: Pathogenic variants in SCN3A, encoding the voltage‐gated sodium channel subunit Nav1.3, cause severe childhood onset epilepsy and malformation of cortical development. Here, we define the spectrum of clinical, genetic, and neuroimaging features of SCN3A ‐related neurodevelopmental disorder. Methods: Patients were ascertained via an international collaborative network. We compared sodium channels containing wild‐type versus variant Nav1.3 subunits coexpressed with β1 and β2 subunits using whole‐cell voltage clamp electrophysiological recordings in a heterologous mammalian system (HEK‐293T cells). Results: Of 22 patients with pathogenic SCN3A variants, most had treatment‐resistant epilepsy beginning in the first year of life (16/21, 76%; median onset, 2 weeks), with severe or profound developmental delay (15/20, 75%). Many, but not all (15/19, 79%), exhibited malformations of cortical development. Pathogenic variants clustered in transmembrane segments 4 to 6 of domains II to IV. Most pathogenic missense variants tested (10/11, 91%) displayed gain of channel function, with increased persistent current and/or a leftward shift in the voltage dependence of activation, and all variants associated with malformation of cortical development exhibited gain of channel function. One variant (p.Ile1468Arg) exhibited mixed effects, with gain and partial loss of function. Two variants demonstrated loss of channel function. Interpretation: Our study defines SCN3A‐ related neurodevelopmental disorder along a spectrum of severity, but typically including epilepsy and severe or profound developmental delay/intellectual disability. Malformations of cortical development are a characteristic feature of this unusual channelopathy syndrome, present in >75% of affected individuals. Gain of function at the channel level in developing neurons is likely an important mechanism of disease pathogenesis. ANN NEUROL 2020;88:348–362